S1P/S1P2 Signaling Axis Regulates Both NLRP3 Upregulation and NLRP3 Inflammasome Activation in Macrophages Primed with Lipopolysaccharide - Chi-Ho Lee (MDPI AG, 2021)
The activation of NLRP3 inflammasome is a key factor for various inflammatory diseases. Here, we provide experimental evidence supporting the regulatory role of sphingosine-1-phosphate (S1P) in NLRP3 inflammasome activation in mouse bone-marrow-derived macrophages (BMDMs), along with the S1P receptor subtype involved and underlying regulatory mechanisms. During the priming stage, S1P induced NLRP3 upregulation in BMDMs only when primed with lipopolysaccharide (LPS). In this event, S1P2, but not S1P1, was involved based on the attenuated NLRP3 upregulation with JTE013 (S1P2 antagonist) or S1P2 knockdown. During the activation stage, S1P induced NLRP3 inflammasome activation in LPS-primed BMDMs via caspase-1 activation, interleukin 1β maturation, apoptosis-associated speck-like protein containing a CARD (ASC) speck formation, and IL-1β secretion. Such NLRP3 inflammasome activation was blocked by either pharmacological inhibition or genetic knockdown of S1P2. NF-κB, PI3K/Akt, and ERK1/2 were identified as effector pathways underlying S1P/S1P2 signaling in the regulation of NLRP3 upregulation in LPS-primed BMDMs. Further, reactive oxygen species (ROS) production was dependent on the S1P/S1P2 signaling axis in these cells, and the ROS generated regulate NLRP3 inflammasome activation, but not NLRP3 priming. Collectively, our findings suggest that S1P promotes NLRP3 upregulation and NLRP3 inflammasome activation in LPS-primed BMDMs via S1P2 and subsequent effector pathways.